Substance Use, Highly Active Antiretroviral Therapy, and Liver Enzymes: Evidence From a Cross-Sectional Study of HIV-Infected Adult Patients Without Comorbidities on HAART in the University of Port Harcourt Teaching Hospital - Anyanwu, Chinwe F.; JohnBull, Tamuno-Olobo; Usman, Ibe M.; Aigbogun, Eric O.; Ochai, Joy; Qasem, Ahmed H.; Alkhayyat, Shadi S.; Alexiou, Athanasios; Batiha, Gaber El-Saber (Frontiers in Reproductive Health, 2021)
This study applied structural equation modelling (SEM) to evaluate the role of substance use (alcohol, smoking, & tradomedicine use) to changes in liver enzymes (AST, ALT, and ALP) levels in HIV-infected adult patients on highly active antiretroviral treatment (HAART) for not less than 1 year. The study was cross-sectional part of a randomised comparative trial (Ref: UPH/CEREMAD/REC/19) involving 129 (46 males and 83 females) HIV-infected adult patients. Liver enzyme levels were determined from analysed blood samples using Clinical Chemistry Analyser (VS10) manufactured by Vitro Scient, while the study determined substance using a reliable (Cronbach alpha = 0.805) rapid-exploratory survey question. Liver enzyme values were further categorised into; normal or abnormal using normal reference ranges; ALT=7-55U/L, AST=8-48U/L, and ALP=40-129U/L). STATGRAPHICS V16.1.11 (StatPoint Tech., Inc.) and SPSS (IBM® Amos V21.0.0, USA) were used to analyse the data. Among the HIV-HAART patients, 27.9% alcohol users, 20.9% smokers, and 20.1% tradomedicine users, and more ALP (71.3%) abnormality than ALT (34.9%) and AST (28.7%). The result from the SEM provided only partial support for our hypotheses of direct substance use effects on liver enzyme levels and abnormalities; with direct association of alcohol with elevated AST (b=0.170, p=0.05), and smoking with higher AST (b=0484, p<0.01) and ALT (b=0.423, p<0.01) values. Tradomedicine use was not directly associated with enzyme elevation and abnormality. In conclusion, ALP abnormality was most common, and there is a close association between elevated ALT and AST, with or without elevated ALP. The study found that HIV-HAART patient who drink or smoke will have at least one or more abnormal transaminases. The possible explanation to the increased risk among HIV-HAART patient could be associated with metabolic pressures and supra-additive effects on the livers.